Cyberbullying Terhadap Kesehatan Mental Remaja Wanita Dengan Latar Belakang Broken Home - Hendra Yohanes; Fitriani Fitriani; Sayyidah Khalillah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cyberbullying is a form of bullying that occurs in cyberspace and can have a negative impact on the mental health of victims. This study aims to analyze the effect of cyberbullying on the mental health of female adolescents who have a broken home background. The research method used is qualitative with a case study approach. Data were obtained through in-depth interviews and observations of ten female adolescents who met the criteria. The results showed that female adolescents with a broken home background are more vulnerable to experiencing mental health disorders due to cyberbullying, including anxiety, depression, and decreased self-esteem. Factors such as lack of emotional support from family and instability of the home environment contribute to this vulnerability.